ANALYSIS OF TRITERPENOID COMPOUNDS AT THE LEVEL OF SOLUTION POLLARITY FROM WATER EXTRACT OF BEAN FRUIT (Phaseulus Vulgaris L) - Ragaya Abd. R Balafif; Yayuk Andayani; Erin Ryantin Gunawan (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2013)
This study aims to analyze the triterpenoid group compounds from solvent partition result extract green bean fruit extract (Phaseulus vulgaris Linn) through increasing solvent polarity level. Extracts of beans was extracted by maceration using a water solvent (1: 18 w / v). The result of preliminary test resulted that the viscous water extract of green beans positively contained triterpenoid, and the result of GC-MS analysis showed that triterpenoid compound was present in the fraction of methanol extract that is tetracyclic triterpenoid type, lanostane: 9,19-cyclolanost-24-en-3-ol ( cycloartenol) which has the molecular formula C30H50O (m / z = 426).